Kinematically Aligned Total Knee Arthroplasty Did Not Show Superior Patient-Reported Outcome Measures: An Updated Meta-analysis of Randomized Controlled Trials with at Least 2-Year Follow-up - Hiyama, Shuhei; Takahashi, Tsuneari; Takeshita, Katsushi (The Journal of Knee Surgery, 2020)
Kinematically aligned total knee arthroplasty (KATKA) was developed to improve the anatomical alignment of knee prostheses, assisting in restoring the native alignment of the knee and promoting physiological kinematics. Early clinical results were encouraging, showing better functional outcomes than with mechanically aligned total knee arthroplasty (MATKA). However, there have been concerns about implant survival, and follow-up at 10 years or more has not been reported. In addition, randomized controlled trials (RCTs) comparing KATKA with MATKA have reported inconsistent results. The current meta-analysis of RCTs with a minimum of 2 years of follow-up investigated the clinical and radiological differences between KATKA and MATKA. A systematic review of the English language literature resulted in the inclusion of four RCTs. The meta-analysis found no significant difference in any of the following parameters: postoperative range of motion for flexion (mean difference for KATKA − MATKA [MD], 1.7 degrees; 95% confidence interval [CI], −1.4 to 4.8 degrees; p = 0.29) and extension (MD, 0.10 degrees; 95% CI, −0.99 to 1.2 degrees; p = 0.86); Oxford Knee Score (MD, 0.10 points; 95% CI, −1.5 to 1.7 points; p = 0.90); Knee Society Score (MD, 1.6 points; 95% CI, −2.8 to 6.0 points; p = 0.49); and Knee Function Score (MD, 1.4 points; 95% CI, −4.9 to 7.8 points; p = 0.66). In addition, there was no significant difference between KATKA and MATKA in the rate of complications requiring reoperation or revision surgery (odds ratio, 1.01; 95% CI, 0.25–4.09; p = 0.99) or in the length of hospital stay (MD, 1.0 days; 95% CI, −0.2 to 2.2 days; p = 0.092). KATKA did not increase the number of patients with poor clinical results due to implant position, particularly for varus placement of the tibial component. In this meta-analysis based on four RCTs with a minimum of 2 years of follow-up, KATKA were only relevant to cruciate retaining TKA and could not be extrapolated to posterior stabilized TKA. Patient-reported outcome measures with KATKA were not superior to those with MATKA.
Keywords: knee osteoarthritis; total knee arthroplasty; kinematically aligned; mechanically aligned; outcomes